Greening of Chambal ravine: Site-specific approach for sustainable development - VERMA, S. K.; SINGH, ANIL K.; SINGH, AKHILESH; PRASAD, JAGDISH (Journal of Soil and Water Conservation, 2022)
The ravines of Chambal, particularly the deep one, are most fragile and suffers heavily on account of erosion. The soils of this tract are sandy loam with low organic carbon and very poorly aggregated. More than >30 t ha-1 yr-1 soil, water (> 70% of rainfall) and nutrient (>350 kg of NPK yr-1) get lost during rainy seasons and the tentacles of ravines keep on penetrating further into fertile lands leading to a demographic change. The loosely held soil particles favours high infiltration rate (> 7cm hr-1) and the high elevation differences between land and river bed create a high gradient for a gushing sub-surface water current towards the river which carries soil with it. The formation of ravine is a very typical hydraulic energy generated phenomena and it can be treated only after a thorough understanding of their formation. However, advancement of ravines can be stopped by adopting an integrated approach of indigenous and innovative technologies based on energy concept. Multistep leveling is one of the very recent and innovative technologies which may prevent all kind of losses. Further improvised gabions structures are also a very economical and suitable conservation method to check/ minimize soil and water losses. Adoption of various kind of modules as silvi–pastoral, silvi–medicinal, agro-horti, agroforestry, silvi-pastoral, silvi-medicinal module are most promising for restoration and conservation of ravine lands. Plantation oriented farming helped in carbon sequestration in soil, enhancing food grain, would further add to economics of farmers without disturbing the land ecology.